27.1k views
5 votes
What is the expression

What is the expression-example-1

2 Answers

5 votes

Answer:

3

Explanation:

To solve this, we need to plug in each of the numbers to the equation.

x = 3, y = - 4, z = - 6


(z-2x)/(y) = (-6-2(3))/(-4)

Let's solve the parenthesis first. - 2 * 3 = - 6.


(-6-6)/(-4)

We then subtract -6 - 6.


(-12)/(-4)

Then, we divide (cancel out the negatives).


-12 / -4 =3

Our final answer is 3. Hope this helps!

User Emed
by
4.6k points
2 votes

Answer:

3

Explanation:

z - 2x

--------

y

Let x = 3 y = -4 and z =-6

-6 - 2(3)

--------

-4

-6 -6

---------

-4

-12

-----

-4

3

User RocketMan
by
5.2k points